Lightning locating system using twisted pair overhead lines - Aulia, Aulia (2010)
Lightning mapping or lightning locating systems are based on several working principles such as the Time of Arrival and the Directional Finder. The country wide lightning locating system (LLS) operated by Tenaga Nasional Berhad Malaysia is able to determine the coordinate of the cloud-to-ground lightning strike with an uncertainty of about 500 m. The LLS is made of high performance sensors positioned throughout the country together with a central processing unit. An alternative method known as the localised lightning locating system (LLLS) is proposed to determine the coordinate of any cloud-to-ground lightning strike within a certain local region. The LLLS is based on the measurement of induced voltages due to lightning strikes in the vicinity of an existing overhead twisted telephone lines. The system consists of twisted pair overhead lines, induced voltage signal transducers, signal transmission cables, and a user friendly processing unit. The overhead lines have been constructed and laid in such a way to form a cartesian system suitable for lightning strike coordinate calculation with a total coverage area of 210 m x 270 m. The processing software which has been programmed in LabView is able to detect and plot the strike locations. Calibration results on the LLLS performance for one axis (y-axis) show less than 1% error of coordinate position. The field measurements in the month of August 2008 showed a significant result of lightning strike activities. Comparing the lightning density detected by the National Lightning Detection Network (NLDN) and the LLLS for the same day, the LLLS has detected more lightning strikes than NLDN. This may be due to the inability of the LLLS to differentiate between valid cloud-ground discharges and other types of discharges. The developed LLLS can be used as an alternative measuring system to determine a lightning strike location within a small area with a better accuracy due to the small coverage area.